Mycoplasma bovis inhibits autophagy in bovine mammary epithelial cells via a PTEN/PI3K-Akt-mTOR-dependent pathway - Xu, Maolin; Liu, Yang; Mayinuer, Tuerdi; Lin, Yushan; Wang, Yue; Gao, Jian; Wang, Dong; Kastelic, John P.; Han, Bo (Frontiers in Microbiology, 2022)
Although autophagy can eliminate some intracellular pathogens, others, e.g., Staphylococcus aureus, Salmonella, Mycoplasma bovis, can evade it. The phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) pathway, a key regulator of autophagy, is involved in initiation and promotion of a range of pathological diseases. As the effects of M. bovis on the autophagic pathway are not well documented, our objective was to elucidate the effects of M. bovis infection on the PI3K-Akt-mTOR cellular autophagic pathway in bovine mammary epithelial cells (bMECs). Ultrastructure of bMECs infected with M. bovis was assessed with transmission electron microscopy, co-localization of LC3 puncta with M. bovis was confirmed by laser confocal microscopy, and autophagy-related indicators were quantified with Western blotting and RT-PCR. In M. bovis-infected bMECs, intracellular M. bovis was encapsulated by membrane-like structures, the expression level of LC3-II and Beclin1 protein decreased at the middle stage of infection, degradation of SQSTM1/P62 was blocked, autophagy of bMECs was inhibited, and PI3K-Akt-mTOR protein was activated by phosphorylation. Furthermore, the tumor suppressor PTEN can inhibit the PI3K-Akt signaling pathway through dephosphorylation of phosphatidylinositol 3,4,5-trisphosphate and may be important for cellular resistance to infection. In the present study, the number of intracellular M. bovis was inversely related to the change in the level of autophagy markers (e.g., LC3-II, SQSTM1/P62) within host cells induced by the low knockdown of Akt or PTEN. We concluded that M. bovis-infected bMECs alleviated cellular autophagy through a PI3K-Akt-mTOR pathway, and that PTEN acted as a protective gene regulating autophagy, a key step in controlling infection.